Preparation of Graphene Nanosheet/Alumina Composites - Wang, Jing; Tong, Xiaocui; Zhang, Jin; Zhang, Jingjing (Asian Journal of Chemistry, 2012)
The introduction of graphene nanosheet into ceramic composites can be forseen the tantalizing foreground. Graphene nanosheet/alumina composite has been prepared by mixing solid powders process and in situ coating process. From the experimental results, it is suggested that in situ coating process overtakes mixing solid powders process at grains size and package density of graphene nanosheets.